Model-based design of adaptive embedded systems - Hamberg, Roelof; Reckers, Frans; Verriet, Jacques; Basten, Twan (Embedded Systems, 2013)
Today's embedded systems have to operate in a wide variety of dynamically changing environmental circumstances. Adaptivity, the ability of a system to autonomously adapt itself, is a means to optimise a system's behaviour to accommodate changes in its environment. It involves making in-product trade-offs between system qualities at system level. The main challenge in the development of adaptive systems is keeping control of the intrinsic complexity of such systems while working with multi-disciplinary teams to create different parts of the system. Model-Based Development of Adaptive Embedded Systems focuses on the development of adaptive embedded systems both from an architectural and methodological point of view. It describes architectural solution patterns for adaptive systems and state-of-the-art model-based methods and techniques to support adaptive system development. In particular, the book describes the outcome of the Octopus project, a cooperation of a multi-disciplinary team of academic and industrial researchers. This industry-as-laboratory project has used the professional printing domain to validate the project results in an industrial context. Model-Based Development of Adaptive Embedded Systems is targeted at both academic researchers and industrial practitioners. It provides state-of-the art surveys of important aspects of adaptive embedded systems, including system architecture, software architecture, system design, and control strategies. These topics are addressed from a systems engineering perspective by researchers from different disciplines including systems engineering, software engineering, control theory, computer science, and electrical engineering with a clear focus on the industrial validation of the research outcome.